2016
DOI: 10.1103/physrevd.94.014013
|View full text |Cite
|
Sign up to set email alerts
|

Resummation of Goldstone boson contributions to the MSSM effective potential

Abstract: We discuss the resummation of the Goldstone boson contributions to the effective potential of the Minimal Supersymmetric Standard Model (MSSM). This eliminates the formal problems of spurious imaginary parts and logarithmic singularities in the minimization conditions when the tree-level Goldstone boson squared masses are negative or approach zero. The numerical impact of the resummation is shown to be almost always very small. We also show how to write the two-loop minimization conditions so that Goldstone bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 89 publications
1
41
0
Order By: Relevance
“…(For further perspectives and developments on this issue, see refs. [19][20][21][22][23][24][25].) The end result can be written as a relation between the tree-level and loop-corrected VEVs:…”
Section: Introductionmentioning
confidence: 99%
“…(For further perspectives and developments on this issue, see refs. [19][20][21][22][23][24][25].) The end result can be written as a relation between the tree-level and loop-corrected VEVs:…”
Section: Introductionmentioning
confidence: 99%
“…Recently a solution was proposed in the context of the Standard Model [27,28] (see also [29][30][31] for recent related work) and then extended to the MSSM [32] which involved resumming (a subset of) the Goldstone boson propagators. An alternative for the Standard Model based on the 2PI effective action was proposed in [33][34][35], where essentially all particle propagators are resummed.…”
Section: Introductionmentioning
confidence: 99%
“…(For an alternative treatment of the necessary basis integral functions, see [9].) When the tree-level Goldstone boson squared mass is small or negative, as indeed occurs in the Standard Model, infrared (IR) divergences or spurious imaginary parts arise in the effective potential, but it has been shown that a resummation of Goldstone boson propagator contributions cures this issue [10,11]; for further development and related perspectives, see [12][13][14][15][16][17][18]. The 4-loop contributions to the Standard Model effective potential at leading order in QCD are also known [19].…”
Section: Introductionmentioning
confidence: 99%